2017
DOI: 10.1007/s00701-017-3201-5
|View full text |Cite
|
Sign up to set email alerts
|

Placement accuracy of external ventricular drain when comparing freehand insertion to neuronavigation guidance in severe traumatic brain injury

Abstract: AndTo the memory of my mother, Rahma.ii ACKNOWLEDGMENTSThanks go first to my advisor, Dr. Judith Marcoux, who supported me in this endeavor. I have always appreciated the trust she has shown in me. Thanks also to the program director of the neurosurgery residency at McGill University, Dr. Jeffrey Atkinson, who has given me the opportunity to have the time for the master study. I also thank the head of the neurosurgery department, Dr. Kevin Petrecca, who supported me to have the funding of this project, and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 44 publications
0
47
0
Order By: Relevance
“…2 The situation becomes even more challenging in patients with aberrant anatomy due to trauma or underlying pathology. 6 The need for multiple passes during EVD insertion performed with the blind freehand technique has also been criticized, 1 because each pass leads to greater injury to the already compromised brain. In addition, an increased number of catheter passes is associated with a higher risk of complications, including hemorrhage and infection.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…2 The situation becomes even more challenging in patients with aberrant anatomy due to trauma or underlying pathology. 6 The need for multiple passes during EVD insertion performed with the blind freehand technique has also been criticized, 1 because each pass leads to greater injury to the already compromised brain. In addition, an increased number of catheter passes is associated with a higher risk of complications, including hemorrhage and infection.…”
mentioning
confidence: 99%
“…In addition, an increased number of catheter passes is associated with a higher risk of complications, including hemorrhage and infection. 1 To address the above-mentioned problems, a precise patient-tailored navigational approach would be very beneficial. 2 The use of image guidance during EVD insertion has been demonstrated to greatly minimize the number of passes required for successful insertion and improve targeting accuracy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…16 With regard to ICPMs, Guyot et al reported no infections in 229 patients who underwent placement of Camino (Integra LifeSciences) intraparenchymal ICP monitors; 27 in addition, rates of infection with concurrent placement of EVDs and ICPMs seem to be similar to those of EVD placement alone. 2,5 To date, the majority of studies reporting VAI rates have been in TBI-predominant patient populations; however, in a large retrospective analysis of 116,813 patients with aneurysmal SAH, 32.9% were managed with EVDs, with a mean annual rate of infection of 7.3%. 48 In a similar retrospective analysis of the Nationwide Inpatient Sample of 34,238 patients with spontaneous intracranial hemorrhage, a subset of patients with VAIs had an overall significant increase in the rate of inpatient mortality, length of stay, and cost of care.…”
Section: Complications Of Invasive Intracranial Pressure Monitoring Dmentioning
confidence: 99%
“…A prospective study that compared EVDs placed with a frameless computer-based neuronavigation guidance system with a retrospective cohort of patients with TBI with EVDs placed freehand found that neuronavigation nearly doubled the likelihood of achieving placement in the ipsilateral lateral ventricle (94.7% vs 57.1%; p = 0.009) and required statistically significantly fewer passes (1.16 ± 0.38 vs 1.63 ± 0.86 passes; p = 0.018). 2 Likewise, Mahan et al found that stereotactic imageguided placement of EVDs in the ICU setting allowed for near perfect catheter placement; ironically, this occurred at the cost of 40 additional minutes to achieve successful ventricular cannulation compared with historical cohorts. 40 The increased time that is required to use image guidance may not be the best management option for patients with impending cerebral herniation issues; however, if time allows, an imaging guidance system may improve the likelihood of optimal placement.…”
Section: Misplacement Of Evdsmentioning
confidence: 99%